Akta Pemberian Hak Tanggungan Terhadap Hak Buruh Dalam Putusan Pailit - Irawan, Dedi (Recital Review, 2020)
The purpose of this study are: 1. To find out how to position holders of security rights and workers’ rights in the event of bankruptcy. 2. To find out how the legal consequences Granting Mortgage Deed which is a product of the Land Deed Official which gave birth to a security interest against labor rights of labor when the company where the work was bankrupt. The formulation of the problem of this paper are: 1. The position of the holders of security rights and workers’ rights in the event of bankruptcy. 2. How does the legal consequences of the deed of award of Encumbrance (APHT) relating to workers’ rights when the company where he worked was bankrupt. The theory that I use in this research discipline theory, the theory of legal certainty and legal protection theory. In this study the authors used normative juridical research method. The results of this study are: 1. The sequence-uratan or the position of the creditors in bankrupt companies are as follows: a.Kreditor whose position at the top stock creditor collateral material (eg tax debt) where the basic law concerning this creditor contained in Article 21 KUP Law in conjunction with Article 1137 of the Civil Code, b. Creditors holders of collateral material are embraced as a creditor Separatists (legal basis of Article 1134, paragraph 2 of the Civil Code). To this day collateral material arranged in Indonesia include: 1.Gadai, 2. Fiduciary, 3. Mortgage, 4. Ship Mortgages. c.Utang the bankruptcy estate, which included the bankruptcy estate debt are as follows: Cost of bankruptcy and the fee Curator, d. Wages, good for a time before the debtor bankrupt and after the debtor bankrupt (Article 39 (2) Labor Law, e. Lease building after the debtor bankrupt and so on (Article 38 paragraph (4) Labor Law. F. Creditors preferred specialty, as contained in Article 1139 Civil Code, and g. general preferred creditors, as contained in Article 1149 of the Civil Code; and f.Kreditur concurrent. lenders in this group are all creditors, including creditors separatists and does not include special or general preferan creditors (Article 1131 in conjunction with Article 1132 Civil Code). Based on the sequence of the separatist position of creditors (holders of security rights) on a preferred creditor (wages). 2. to the right of workers indirectly have to wait for the division of the ha-existing rights thereon, in other words the right of workers have reduced by taxes, creditors collateral holder material (creditors separatists), bankruptcy costs and fees Curator.